Hubungan Lingkar Pinggang dan Indeks Massa Tubuh Karyawan PT’X terhadap Risiko Obesitas Sentral pada Laki-laki Usia Produktif - Dewi, Maharani Kusuma (Nindikayla Institute, 2024)
This study aims to investigate the relationship between waist circumference (WC) and Body Mass Index (BMI) with the risk of central obesity (OS) in productive-age male employees at PT 'X'. This descriptive case study was conducted in 2024, involving the analysis of company policy data and employee anthropometric measurements. Data collection methods included a review of the company's health and nutrition policies, and measurement of WC and BMI in the productive-age male employee population. Data were analyzed to determine the distribution of WC and BMI, and to identify the level of OS risk based on established criteria. The results showed a positive correlation between WC and BMI with OS risk, indicating that an increase in both parameters contributes to an increased risk of OS in the studied population. These findings were integrated with existing health and nutrition policies at PT 'X', identifying areas for improvement and practical recommendations for intervention. The implications of this case study emphasize the importance of routine anthropometric monitoring and the implementation of a comprehensive wellness program to manage OS risk and improve employee health.